The Emergence of Modern Shi‘ism - Liyakat Takim (International Institute of Islamic Thought, 2017)
This is the first comprehensive work on the origins, development, and sociopolitical ramifications of the Usuli movement within Twelver Shi‘ism. Given that Wahid Bihbahani (1709-91), the founder and catalyst for Usuli revivalism during the nineteenth century, is barely known in the West, it is a welcome addition to the growing Western literature on medieval and modern Shi‘ism. This ongoing movement is the most powerful force in Twelver Shi‘ism. Using a wide range of primary and secondary sources, Heern highlights the emergence of modern Usulism during the eighteenth and nineteenth centuries. While locating its genesis within a global context, he outlines its ideological roots, historical background, and development. His central argument is that Usulism was a response to the ummah’s changing sociopolitical conditions and part of a wider trend of Islamic reform and revivalist movements that began in the eighteenth century. He maintains that its emergence enabled the Shi‘i clerical establishment to attain sociopolitical and economic ascendancy in Iran and Iraq, and that the movement survived without government patronage by cultivating transnational links with the Shi‘i laity. For him, Shi‘i Islam’s recent ascendancy is the result of the neo-Usuli movement ...